Emerson’s Vision of America in John Ford’s "Stagecoach" - Michael Forest (Aesthetic Investigations, 2020)
When Ralph Waldo Emerson addressed the Phi Betta Kappa Society in 1837 at Harvard College, his directives included the establishment of an American literary tradition derived from the unique experience of his fellow citizens in a new context that included a wild frontier. He sought to establish a different moral foundation built on a romantic sense of spiritual attachment to nature. This essay extends the new American grain and ground Emerson’s directives in a truly original and unique American artistic genre – the western film. My thesis is simply that John Ford’s elevation of the western film to artistic status with 1939’s Stagecoach is a uniquely appropriate fulfilment of Emerson’s call in the “American Scholar” for genre elevation, literary nationalism, romantic moral sentiment, and ultimately for confirming an American mythology that articulated and reinforced a native self-identity.